(untitled) (Proceedings of The International Conference on Economics and Development, 2017)
The objective of the study is examine the how the help fruit village program for eradicate rural poverty. The study conducted under the hypothesis of “Fruit village program very helpful to eradicate all forms of rural poverty”. Using mini survey study checked the whether the relationship between poverty eradication of fruit village program. Test the final development outcome of the farmers such as health, infrastructures, education, and livelihood and increase the income of the farmers. Data collected using random sampling method and interviewee farmers and try to use data for develop policy creation based with the final results of the study. The results of the study is very can’t believe because of the papaw cultivation are ongoing and farmers are earning money well and they use income for maintain their life very good condition. Actually they live without any poverty highlights. But their method of income book keeping and attitudes of the income are not very satisfied and most of are ideally neutral about satisfaction. And they don’t know about separately identified the income, house hold expenses and real profit calculation. Also they have no idea about how to maintain quality of papaw cultivation with appling new technology with post-harvest technology for achieve hi income.